A FIRO-B analysis of social skill preferences among auditors. (1st January 2012) - Karim, Khondkar E.; Lessard, Jeffrey P.; Siegel, Philip H.
This study investigates the relative significance of both the social interaction index (SII) and demographic variables by analysing their association to the likelihood in classifying an auditor as internal or external to the firm. This study uses the psychometric technique of the fundamental interpersonal relationship orientation-behavior (FIRO-B) to analyse and compare the social interaction preference of certified internal auditors (CIAs) working for US corporations and certified public accountants (CPAs) employed by public accounting firms. Surveys were developed using the FIRO-B instruments and sent to internal auditors from US corporations located in the western and southeastern sections of the USA. The results of the study show that the scores of the two groups are significantly different. Internal auditors reported lower social interaction preferences than the public accountants.